A closed-loop and scalable process for the production of biomass-derived superhydrophilic carbon for supercapacitors. Issue 9 (21st April 2021) - Fu, Rong; Yu, Chang; Li, Shaofeng; Yu, Jinhe; Wang, Zhao; Guo, Wei; Xie, Yuanyang; Yang, Le; Liu, Kunlun; Ren, Weicheng; Qiu, Jieshan
Abstract : A closed-loop and scalable approach was presented to synthesize biomass-derived carbon materials with superhydrophilic features for high-performance supercapacitors. Abstract : Biomass-derived porous carbon materials with superior wettability towards electrolytes are promising as electrodes for commercial supercapacitors (SCs), but the traditional synthetic processes result in serious environmental pollution and energy consumption. Herein, we propose an innovative closed-loop and scalable process for the production of B/N/O tri-doped superhydrophilic carbon derived from biomass. The adopted boric acid serves as a recyclable and inducing agent due to the reversible conversion between boric acid and boron oxide, further completing the closed-loop route for the production of biomass-derived superhydrophilic carbon. The as-made materials present a two-dimensional (2D) sheet-shaped structure and abundant pores; also, the B, N and O heteroatoms that are in situ introduced into the skeleton of carbon improve the surface hydrophilicity of the fabricated carbon. Benefitting from the synergistic effects of the hierarchical porous morphology, the superhydrophilicity and the multi-doping surface chemistry features of the resultant materials, the penetration, transport and interaction of electrolyte ions within the as-fabricated carbon electrodes would be highly improved. Thus, a favorable electrochemical performance of the supercapacitor is obtained, which can deliver a specific capacitance up to 296 F g −1 @0.5 A g −1 in an aqueous electrolyte. This synthetic strategy with simple operation and mild conditions will be an efficient and potential way to accomplish the widespread application of biomass-derived superhydrophilic carbon in supercapacitors.